2007
DOI: 10.1538/expanim.56.273
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Deficiency of Germfree Mice Caused by Feeding Standard Purified Diet Sterilized by .GAMMA.-Irradiation

Abstract: Abstract:Germfree mice died when they were fed a purified diet of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…The majority of vitamin K homologue in the liver is vitamin K2, which has strong biological activity in the synthesis of coagulation factor [3,15], however, the plasma vitamin K2 level is less than the vitamin K1 level in normal rats [10]. In our study, the blood vitamin K2 level was also less than the vitamin K1 level in reported that vitamin K in diet was reduced by γ-radiosterilization [17]. Therefore, in the present study there is a possibility that vitamin K in the diet was sham-operated rats.…”
Section: Discussioncontrasting
confidence: 47%
“…The majority of vitamin K homologue in the liver is vitamin K2, which has strong biological activity in the synthesis of coagulation factor [3,15], however, the plasma vitamin K2 level is less than the vitamin K1 level in normal rats [10]. In our study, the blood vitamin K2 level was also less than the vitamin K1 level in reported that vitamin K in diet was reduced by γ-radiosterilization [17]. Therefore, in the present study there is a possibility that vitamin K in the diet was sham-operated rats.…”
Section: Discussioncontrasting
confidence: 47%
“…Macronutrients such as carbohydrates, proteins, and fats are generally insensitive to irradiation, but some vitamins including A, K, B1, B6 and B12 are fairly sensitive. 32 Irradiation levels nearing the legal maximum may significantly reduce the contents of these vitamins and cause clinical signs 7,21 unless the feed is fortified after irradiation, further adding to the cost of the feed.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial resistance to sterilization by irradiation has been linked to microbiological burden, moisture level, oxygen content, and temperature of the product (Halls, 1992;Hanson and Shaffer, 2001). Vitamin deficiencies also have been reported with irradiated diets (Caulfield et al, 2008, Hirayama et al, 2007. Vitamin deficiencies also have been reported with irradiated diets (Caulfield et al, 2008, Hirayama et al, 2007.…”
Section: Ionizing Radiationmentioning
confidence: 91%
“…Gamma irradiation offers advantages in economy and convenience over autoclaving and has been used to sterilize food and bedding for gnotobiotic animals for many years (Barc et al, 2004;Cahenzli et al, 2013;Caulfield et al, 2008;Cherbuy et al, 2010;Corpet et al, 1989;Gianni F, personal communication, October 2013;Hartmann et al, 2000;Hirayama et al, 2007;Hudcovic et al, 2009;Ley et al, 1969;Mabrok et al, 2012;Matsumoto et al, 1988;Mwangi et al, 2010;Paterson and Cook, 1971;Rabot et al, 2010;Respondek et al, 2013;Wrzosek et al, 2013;Yamanaka et al, 1977). Many users also consider irradiation to be more reliable than autoclaving, especially with difficult materials such as pelleted chow, and a few have replaced autoclaving entirely with irradiation (F. Gianni, personal communication, January 2014).…”
Section: Ionizing Radiationmentioning
confidence: 99%